Reconversion(s) territoriale(s) sur l’avenue de Kurtuluş - Cilia Martin (EchoGéo)
The neighborhood of Kurtuluş, heritage of the ancient village of Tatavla, was formed and developed till the mid of the 20th century. From 1950, along with the departure of the Rum minorities, which were considered till that time as quasi majorities, and with the arrival of Anatolian migrants, considerable demographical ruptures were provoked. Thoses mobilities create a diversity of territorial modes and give birth to new centralities, seen also throughout the commerce and recently from within the memorial strategies which rebuild the rum past of the neighborhood. Finally, those territorialities participate to the recomposition of the neigborhood and will be analysed through the scale of a headlight avenue, the avenue of Kurtuluş.